IDENTIFIKASI JENIS-JENIS ANGGREK (Orchidaceae) DI HUTAN LARANGAN ADAT IMBO PUTUI DESA PETAPAHAN KECAMATAN TAPUNG KABUPATEN KAMPAR - Munzil Azim; Defri Yoza Yoza; Yossi Oktorini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Natural orchid has not yet undergone crossbreeding that is still living naturally in attached forest habitats with humidity, light intensity, and soil conditions suitable for orchid growing needs. The purpose of this research was to see all types of orchids (Orchidaceae) and orchid habitat (Orchidaceae) in Imbo Putui Banned Indigenous Forest, Petapahan Village, Tapung District, Kampar Regency. The research was conducted in Imbo Putui Banned Indigenous Forest, Petapahan Village, Tapung District, Kampar Regency, Riau Province. This study used a purposive sampling technique using an exploration method system based on canopy density. The research location's total area is 6 Ha with three lines so that the line of observation has an area of 1000 m with a width of 20 m (10 m left and 10 m right). The results showed that in Imbo Putui Banned Indigenous Forest, and there were five types of orchids from 4 orchid genera, namely Merpati Orchid (Dendrobium crumenatum), Bamboo Orchid (Bromheadia finlaysoniana), Board Orchid (Cymbidium dayanum), Vanilla (Vanilla tahitiensis), and Vanilla sp. The species diversity index (H ') of orchids in Imbo Putui Banned Indigenous Forest is low with a species diversity value of 1.55, and habitat characteristics are tropical orchids with four types of epiphytes, 1 type of terrestrial orchid and inceptisol soil type, low rainfall, sunlight intensity of 554,49 lux, the temperature of 30,3 oC and humidity of 66%. Keywords : Banned indegoeus forest, habitat, orchid